Marine sponge‐derived smenospongine preferentially eliminates breast cancer stem‐like cells via p38/AMPKα pathways - Jie Tang; Wei Wu; Fan Yang; Liyun Liu; Zhen Yang; Li Liu; Weizhuo Tang; Fan Sun; Houwen Lin (Cancer Medicine)
Abstract Breast cancer stem cells (CSCs) have been postulated as responsible for therapeutic failure of breast cancer. Novel agents effectively targeting breast CSCs are urging to be discovered to overcome cancer relapse and metastasis. We recently established a CSC‐like model through ectopic expression Nanog, a core pluripotency factor, in breast cancer cells and validated induced CSC‐like (MCF7‐Nanog) model acquired stem‐like properties. Using this model, we found that smenospongine (Sme), a natural sesquiterpene aminoquinone isolated from marine sponge Spongia pertusa Esper, preferentially inhibited the induced CSC‐like cells proliferation by inducing G0/G1 arrest and intrinsic apoptosis via increasing the phosphorylation level of p38 and AMPKα. Importantly, Sme exhibited the ability to abrogate CSC‐like cells associated with a downregulation of stem cell markers including Nanog, Sox2, and Bmi1. Functionally, Sme inhibited the ability of MCF7‐Nanog cells to form tumor sphere in vitro and develop tumor in vivo. Significant antitumor effects are observed in Sme‐treated mouse xenograft tumor models, with no apparent toxicity to mice. Taken together, our findings provide a CSC‐like model to identify novel CSC‐targeting drugs and identify Sme as a candidate natural agent for treatment of breast cancer.